The Prevalence and Determinants of Exclusive Breastfeeding during First Three Months of Infant's Life in Bushehr, Iran: A Cross-sectional Community-based Study - Fatemeh Najafi-Sharjabad; Salimeh Mohammadi (Mashhad University of Medical Sciences, 2021)
Background & aim: Breastfeeding is one of the most effective strategies to reduce infant and child mortality around the world. Due to the low rate of exclusive breastfeeding in Bushehr, Iran, it seems necessary to examine its related factors. Therefore, this study aimed to investigate the prevalence and factors associated with exclusive breastfeeding in Bushehr, Iran. Methods: This study was conducted based on a cross-sectional descriptive design. The data were collected using an adopted and validated structured questionnaire from 288 mothers who attended 10 public health centers through stratified random sampling in Bushehr, Iran, during 2019. The obtained data were analyzed in SPSS software (version 24) through descriptive statistics, Chi-square test, t-test, and binary logistic regression. Results: The mean age of the respondents was 28.48±5.50 years, and the prevalence of exclusive breastfeeding during the first three months of the infant's life was obtained at 75%.  Lower household income was associated with higher exclusive breastfeeding practice (OR: 2.21, 95% CI: 1.01-4.69.95; P= 0.04). The odds of exclusive breastfeeding practice was 2.15 times higher in mothers who were satisfied with their newborn's sleep habits (OR: 2.15, 95% CI: 1.14-4.04; P =0.01); moreover, the corresponding value was 9.82 times higher in mothers with singleton pregnancy (OR: 9.82, 95% CI: 1.78-24.12; P=0.009). Mothers who had a sick infant were 0.45 times less likely to practice exclusive breastfeeding, compared to those who had a healthy infant (OR: 0.45, 95% CI: 0.212-0.950; P=0.03). Conclusion: Household income, mother's satisfaction with newborns sleep habits, singleton pregnancy and infant disease were associated with exclusive breastfeeding practice. It is recommended to identify mothers who are in high-risk groups and consider their needs to promote exclusive breastfeeding.